Desempenho funcional, capacidade física e fatores associados em idosas com dor lombar aguda: dados do estudo multicêntrico Back Complaints in the Elders (BACE-Brasil) - Diogo Carvalho Felicio (2015)
Population aging is a prominent worldwide phenomenon. Low back pain (LBP) is one of the most prevalent pain complaints in the elderly and among the adverse outcomes highlight the functional decline. The updated version of the International Classification of Functioning, Disability, and Health conceives the functionality as a result of the dynamic combination between health conditions and contextual factors. Knowing the variables that affect the functionality of the elderly can enable therapeutic interventions in modifiable factors and contributes to the non-recurrent or chronic pain. The purpose of this doctoral thesis was to evaluate the functional performance, physical capacity and associated factors in elderly with acute LBP. This was an ancillary study of the Back Complaints in the Elders study (BACE), a longitudinal observational epidemiological research project by an international consortium involving Brazil, the Netherlands, and Australia. This thesis was prepared in accordance with standards established by the board of the Post Graduate Program in Rehabilitation Sciences, Federal University of Minas Gerais. Its structure includes an introduction covering the contextualization, objectives and background of the study; the methodology that describes the methods used; the third part contains three articles, which are the end products of this thesis. The first article entitled "Handgrip is not a predictor of disability among elderly women with acute low back pain: a longitudinal multicenter study Back Complaints in the Elders (BACE) - Brazil was prepared and formatted according to the standards of the Brazilian Journal of Physical Therapy, for which it was submitted. The results indicated that handgrip can not be generalized as a predictor of disability among elderly women with acute low back pain. The second article Anterior trunk mobility does not predict disability among elderly women with acute low back pain: Back Complaints in the Elders - Brazil Study Results was submitted to the Physical Therapy Journal. Our findings suggested that the range of motion and disability are independent clinical parameters that are not associated. The third article Kinesiophobia is not associated with disability among elderly women with acute low back pain: Back Complaints in the Elders - Brazil Study Results was submitted to the The Spine Journal. We note that the kinesiophobia is not associated with the disability among elderly with acute low back pain. Finally, the conclusions, the scientific production and the post-textual elements are show.